Edukasi dan Pelatihan Pencegahan Stunting pada Balita dengan Membuat Makanan Berbahan Lokal di Desa Baregbeg - Asri Aprilia Rohman; Nina Rosdiana; Ade Sity Riyantina; Yoga Ginanjar; Agus Mulyana; Ai Liani; Dea Rismalinda; Nova Sri; Wulan Cahya Utami (Yayasan Inspirasi El Burhani, 2023)
Introduction: Stunting is a condition where the body is short due to insufficient nutritional intake or recurrent infections that occur in the golden periode. Stunting is influenced by several factors, on of which is the mothers knowledge about nutritions. One of the interventions to prevent stunting can be carried out through education and training to prevent stunting through locally sourced food such as using fish and moringa leaves, so that nutritional intake for toddlers can be adequate and can reduce the risk of stunting. Objective: Participants in this activity totaled 35 people Method: The methods used in this community service are lectures, discussions and demonstration of food processsing from local food ingreadients Result: Based on the results of the education and training, it is hoped that participants will have knowledge and skills to use local food ingredients to prevent Stunting Conclusion: Based on the community service activities that have been ccarried out, it can be concluced that this activity has been carried out according to plan and stages with 35 participants attending from the Baregbeg area. The participants were very enthusiastic about participating in the activity from start to finish. From this activity, posyandu cadres and mother of toddlers gained knowledge and skills regarding stunting prevention by making food preparations made from local fish and moringa leaves.